2012
DOI: 10.1155/2012/717398
|View full text |Cite
|
Sign up to set email alerts
|

Air Turbines for Wave Energy Conversion

Abstract: This paper describes the present status of the art on air turbines, which could be used for wave energy conversion. The air turbines included in the paper are as follows: Wells type turbines, impulse turbines, radial turbines, cross-flow turbine, and Savonius turbine. The overall performances of the turbines under irregular wave conditions, which typically occur in the sea, have been compared by numerical simulation and sea trial. As a result, under irregular wave conditions it is found that the running and st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 91 publications
(53 citation statements)
references
References 25 publications
0
53
0
Order By: Relevance
“…Firstly, the pressure loss coefficient of C p containing the S corresponding to the product of the tank width and the air chamber length can be calculated by Equation (4), and the turbine pressure coefficient of ψ is determined by Equation (3) which is composed of the total pressure drop ∆p and the axial flow velocity v a . The ∆p and v a are the experimental results obtained by the preliminary turbine test [18]. Moreover, the total pressure difference at the nozzle is equal to the total pressure drop at the turbine (∆p N = ∆p), and the flow rate in the turbine is the same as in the case of the nozzle (Q = v a S T = v N S N ).…”
Section: Experimental Apparatusmentioning
confidence: 99%
See 2 more Smart Citations
“…Firstly, the pressure loss coefficient of C p containing the S corresponding to the product of the tank width and the air chamber length can be calculated by Equation (4), and the turbine pressure coefficient of ψ is determined by Equation (3) which is composed of the total pressure drop ∆p and the axial flow velocity v a . The ∆p and v a are the experimental results obtained by the preliminary turbine test [18]. Moreover, the total pressure difference at the nozzle is equal to the total pressure drop at the turbine (∆p N = ∆p), and the flow rate in the turbine is the same as in the case of the nozzle (Q = v a S T = v N S N ).…”
Section: Experimental Apparatusmentioning
confidence: 99%
“…The flow rate Q was measured by the velocity meter (KANOMAX 6501) at the fan duct. In Figure 5, D = 0.30 m denotes the result of the conventional turbine test without the air chamber and the elbow measured by Takao et al [16,18] …”
Section: Effect Of Air Chamber Lengthmentioning
confidence: 99%
See 1 more Smart Citation
“…Setoguchi et al [9,10] reviewed a variety of experimental results concerning the performances of the Wells turbine and the impulse turbine. Besides, Takao et al [11] showed that the impulse turbine was superior to the Wells turbine in a wide flow rate range. On the other hand, there are the studies about the performance of the OWC with the turbine [12], but the most studies make mention of the performance of the OWC with the Wells turbine.…”
Section: Introductionmentioning
confidence: 99%
“…As discussed elsewhere [ of computational fluid dynamic (CFD) analysis to study the impulse turbine for the 500 kW Yongsoo OWC plant. Takao and Setoguchi [6] provided an overview of current research results on air turbines and made recommendations for basic geometric parameters. Liu et al [7,8], by focusing on numerical simulations of an optimized impulse turbine under steady flow conditions, established a complete system and a series of procedures to achieve higher turbine efficiency.…”
Section: Introductionmentioning
confidence: 99%